COVID-19 vaccination status and factors associated with deaths from the disease, Vitória, 2020-2023: cross-sectional study - Tatiane Comerio; João Paulo Cola; Keila Cristina Mascarello; Carolina Maia Martins Sales; Brenda Silva Freire; Adjane da Silva Vasconcelos; Marcia Christina de Souza; Ethel Leonor Noia Maciel (Epidemiologia e Serviços de Saúde)
Abstract Objective To analyze the vaccination status against COVID-19 and factors associated with deaths from the disease. Method Cross-sectional study with secondary data on deaths from COVID-19 in the city of Vitória, Espírito Santo, between February 2020 and December 2023. Individuals under 18 years of age and those with unavailable vaccination status were excluded. Relative and absolute frequencies were calculated by vaccination status. Poisson regression was used to calculate crude and adjusted prevalence ratios (PR) and 95% confidence intervals (95% CI). Results A total of 1,460 deaths were included, of which 244 (16.7%) had received ≥2 doses of the vaccines. Among the unvaccinated individuals, the highest frequency of deaths was recorded in individuals aged 60 to 79 years (47.9%), male (56.4%), and non-white race/skin color (53.0%). The PR of death in vaccinated individuals was higher in people ≥80 years old (PR 5.55; 95%CI 2.92; 10.55), 60-79 years old (PR 3.61; 95%CI 1.95; 6.69), with chronic lung disease (PR 1.35; 95%CI 1.03; 1.78) or chronic neurological disease (PR 1.37; 95%CI 1.08; 1.72), respiratory distress (PR 1.51; 95%CI 1.02; 2.23), desaturation (PR 1.97; 95%CI 1.35; 2.88) and adynamia (PR 2.80; 95%CI 2.02; 3.90). People with 1-4 years of schooling (PR 0.63; 95%CI 0.44; 0.90), 5-8 years of schooling (PR 0.57; 95%CI 0.39; 0.84), ≥8 years of schooling (PR 0.66; 95%CI 0.45; 0.97) had a lower prevalence. Conclusion The highest prevalence of deaths among vaccinated individuals was associated with age ≥60 years, chronic lung or neurological disease, respiratory distress, desaturation, and adynamia. Loss of immunological memory in the elderly indicates the need for vaccine boosters to prevent deaths.